Clinical study of ventilator-associated pneumonia in tertiary care hospital, Kolhapur, Maharashtra, India - Deshmukh, Babasaheb; Kadam, Suhas; M., Thirumugam; K., Rajesh (International Journal of Research in Medical Sciences, 2017)
Background: Ventilator‑associated pneumonia (VAP) is the most common nosocomial infection acquired by patients admitted in the intensive care unit (ICU). However, there is very less information or clinical data available on the occurrence of VAP in Kolhapur, Maharashtra. Methods: study aims to determine the Incidence of VAP in ICU, to study the association between causative microorganism and sensitivity, and to study the association between prognosis and incidence of VAP. Settings and Design: Tertiary level, medical‑surgical ICU; prospective, observational study. Results: Patients coming to Medicine Department of the hospital subjected to mechanical ventilation for more than 48 hours in critical Care Facility during the period of two years May 2014 to April 2016. Conclusions: In the incidence of VAP was found to be 78% among ICU patients. Majority (36%) patients had diabetes mellitus, 30% had hypertension before the admission. It is observed that chances of developing VAP were more in patients with co-morbid conditions. The microbiological results of Endotracheal Aspirate showed that, majority 36% had pseudomonas, 26% had Acinetobacter, 22% had no growth, 14% staphylococci (Staphylococcus is a gram-positive, round-shaped bacterium that is a member of the Firmicutes, and is frequently found in the nose, respiratory tract, and on the skin), 2% proteus mirabilis as compared to similar studies. Out of all, Pseudomonas is the most commonly isolated organism. This could be attributed to decreased immunity and a compromised general condition due to associated illness. Also, prolonged hospital stay is also of significance.